The phenomenology of customer delight: a case study of product evaluation - Burns, Andrew Douglas (Cranfield University, 2003)
This thesis presents a phenomenological case study of customer delight during product evaluation. The literature presents two existing 'theories' of customer delight. The first, from the field of Consumer Research, presents a cognitive model of post-purchase customer delight as the affective result of expectation disconfirmation. The second, from the Manufacturing literature, proposes that customers are delighted when products contain unexpected features or levels of qualities that exceed expectations. This research was motivated by the fact that our current understanding of this commercially important phenomenon is confined by expectation-based thinking. Furthermore, both streams of research have neglected to study the naturalistic occurrence of delight from the customer's perspective. The aim of this research was to generate an integrated understanding of the affective, behavioural, and cognitive nature of customer delight and its product basis. A case study methodology, incorporating interview, self-report and observational methods, was adopted to generate a triangulated understanding of productbased customer delight. The naturalistic product evaluations of 918 customers were observed and self-reported delight reactions were collected from 66 research participants. In total 414 customer delight reactions were analysed in detail. This approach aimed to generate new theory, rather than test the existing models, and this new integrative understanding of customer delight is the primary contribution of this thesis. A new model of product-based customer delight is presented, and the existing Manufacturing model is extended to incorporate the empirical findings of the case study. Whilst the findings of this research support concepts contained within the existing theories of customer delight, they also demonstrate their limitations. The cognitive and affective diversity of customer delight reactions, previously unaccounted for in the literature, was uncovered and five product-based routes to delight were identified. The emergent theory successfully integrates the two previously separate concepts of delight and builds upon them by identifying the behaviours associated with customer delight resulting from both attribute-based and holistic product appraisals.